Effect of carbonation curing on distribution and binding capacity of chloride ions in cement pastes. (15th July 2023) - Sun, Ming; Sun, Congtao; Zhang, Yuguo; Geng, Yuanjie; Fan, Liang; Liu, Nazhen; Zhang, Peng; Duan, Jizhou; Hou, Baorong
Abstract: Carbonation curing of concrete is an effective measure to reduce CO2 emissions, but it can adversely affect chloride binding capacity of cement pastes and its durability. In this study, the chloride ion content and phase assemblages of cement pastes under three curing conditions: standard curing, carbonation curing, and mixed curing (7-day carbonation curing and 21-day standard curing) were investigated based on combined macroscopic and microscopic methods. The chloride ions were introduced into cement pastes either through internal incorporation during the mixing process or from external penetration during its immersion in chloride contained solutions. Experimental results show that a large number of internally incorporated chloride ions were accumulated in the surface layer of pastes due to moisture evaporation during carbonation curing process. The transport of internally incorporated chloride ions in the paste under the mixed curing process was affected by the coupling effects of carbonation and capillary suction, resulting in inward migration of chloride ions. The external chloride ions from the solution penetrated into paste through initial diffusion and subsequent capillary suction during carbonation curing and mixed curing processes. Neither internally-incorporated nor externally-penetrated chloride ions could be bound in the carbonated zone, and the Friedel's salt could not be formed either. Due to the decrease of carbonation effect along the penetration depth and inward migration of chloride ions, the bound chloride ion content increased and formed a peak value in the inner layer. Highlights: Moisture evaporation under carbonation curing helped the accumulation of internal chloride ions in the surface layer. The internally-incorporated chloride ions mainly migrated inward during mixed curing process. Neither internally nor externally introduced chloride ions could be bound in the carbonated zone.